AHMAD DAHLAN EDUCATIONAL METHODOLOGY IMPLICATIONS FOR INDONESIA’S CONTEMPORARY EDUCATION - Rahmasari, Zulfa; Irwanto; Hirza, Ni’matul (Prodi Pendidikan Agama Islam STAI Darul Falah, 2025)
Islamic refreshes in the conflicting eastern worlds such as Egypt, India, Turkey, and Pakistan have had the same impact in Indonesia. This update is due to the resentment and dissatisfaction of the figures with the educational system that has been running. This research aims to learn about Ahmad Dahlan's educational methodology and his thoughts about how education should be carried out which will have implications for contemporary education in Indonesia, including in the LPQ Darul Muta’allimin Semarang. The research is done through a case study. The data obtained is sourced from the interview, participant observation, documentation, and also from textbooks, scientific articles, and journals as supportive data. Data is analyzed through Creswell's technique which preparing, reading, coding, describing, and interpreting data. The research findings showed that Ahmad Dahlan one of the pioneers of Islamic education in Indonesia, combines the educational system of the boarding schoolhat only studies the science of religion, with the system of education that is secular colonial and only studies general science. Ahmad Dahlan's educational methodology is the method of lectures, analogy, discussion or questioning, democratic humanistic methods, and methods of practice. The implications of Ahmad Dahlam's educational methodology in contemporary education in Indonesia are the consolidation of religious education subjects as a compulsory curriculum in schools.LPQ Darul Mutaallimin as a Quranic educational institution through the obligation to own an operational permit, has been recognized by the government and has the same rights as other formal educational institutions. On the other hand, Ahmad Dahlan reforms also the emergence of Indonesia's first private hospital as a result of the al-maun movement, as well as the establishment of schools that specialize in specific fields.